Evaluation of mechanical properties of unbound granular materials for pavements and rail tracks - Correia, A. Gomes (2004)
This paper describe the experimental determination of the stress-strain properties, stiffness and permanent deformations under cyclic loading, mainly for compacted unbound granular materials in pavement and rail track structures. In particular the following aspects are described in detail: assessment in laboratory and in field of mechanical parameters for pavement design and construction, importance of effective stress analysis of unsaturated materials, design of pavement foundation taking into account non linear behaviour of unbound granular materials, classifications to ranking materials against mechanical performances and comparison of modulus obtained by different field tests.